2013
DOI: 10.1007/s11424-013-2282-3
|View full text |Cite
|
Sign up to set email alerts
|

Basketball scoring in NBA games: An example of complexity

Abstract: Scoring in a basketball game is a process highly dynamic and nonlinear type. The level of NBA teams improve each season. They incorporate to their rosters the best players in the world. These and other mechanisms, make the scoring in the NBA basketball games be something exciting, where, on rare occasions, we really know what will be the result at the end of the game. We analyzed all the games of the -10 NBA regular seasons (6150 games). We have studied the evolution of the scoring and the time intervals betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Thus, this evolving trend could also be related to changes in the competitiveness of NBA seasons. However, studies have suggested that the competitive balance in NBA is stable over time and close to its average [14,16] and that the scoring process is well described by a nearly unbiased random walk [9], suggesting that NBA teams are quite balanced. Furthermore, a decrease in the intensity of home advantage over time was also observed by Jamieson [66] for several sports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this evolving trend could also be related to changes in the competitiveness of NBA seasons. However, studies have suggested that the competitive balance in NBA is stable over time and close to its average [14,16] and that the scoring process is well described by a nearly unbiased random walk [9], suggesting that NBA teams are quite balanced. Furthermore, a decrease in the intensity of home advantage over time was also observed by Jamieson [66] for several sports.…”
Section: Resultsmentioning
confidence: 99%
“…The former aspect along with a comparison between men and women soccer leagues was also discussed by Pollard and Gómez [78]. There are also evidence that home advantage is more intense at the beginning of basketball matches [51], time dependent for handball [58], and that the scoring processes is highly dynamic [16] for basketball. All these features raise several questions on the microscopic effects of the home advantage, and also on how these features may possibly differ among teams and time era.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although there is increasing interest in quantitative analysis and modeling in sports [32][33][34][35][36], many questions remain about what patterns or principles, if any, cut across different sports, what basic dynamical processes provide good models of within-game events, and the degree to which the outcomes of games may be predicted from within-game events alone. The comprehen-sive database of scoring events we use here to investigate such questions is unusual for both its scope (every league game over 9-10 seasons), its breadth (covering four sports), and its depth (timing and attribution information on every point in every game).…”
Section: Discussionmentioning
confidence: 99%
“…Este conjunto de características podrían favorecer que la NBA tenga una mayor atracción para los aficionados de todos los equipos, al existir mayores evoluciones de los equipos en cuanto a las posiciones finales a lo largo de las temporadas. Recientes estudios muestran una gran incertidumbre en cada uno de los encuentros de la NBA, con una gran aleatoriedad en los vencedores (de Saá Guerra et al, 2013).…”
Section: E P O R T Eunclassified